FOREIGN DIRECT INVESTMENT AND EXPENDITURE ON EDUCATION RELATIONSHIP WITH EMPLOYMENT RATE IN UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article shows the positive relationship between government spending on education and the level of employment of the population in Uzbekistan. Analyzes of econometric models The level of economic activity of the population in the Republic of Uzbekistan, direct investments from abroad, economic and economic sectors spent on education were analyzed. Scientific suggestions and recommendations are also made for ensuring the employment of the population with education in the economic development of the country.
Keywords: economic employment of the population, foreign direct investment, education, econometric model, economic activity.